Desenvolvimento de sistema polimérico a base de turfas e substâncias húmicas para liberação lenta de nutrientes para plantas - Melo, Camila de Almeida [UNESP] (2014)
One of the main current challenges of the fertilizer industry is to try to combine, in a single product, two ingredients so necessary for good plant growth: organic matter and nutrients, in order that nutrients are available depending on the need of the plants avoiding environmental problems caused by excess thereof. Thinking about this, the aim of this study was to develop and evaluate the use of peat and peat humic substances enriched with the micronutrients Cu, Co, Fe, Mn, Ni and Zn in the slow release of these nutrients in a aqueos and soil/plant system. Two peat samples from region of Sergipe (TSA and TSI) were used as well as the humic substances from both samples (TSA-SH and TSI-SH). The samples were characterized by several techniques including CHN, FTIR, NMR, TG and MEV. The best conditions for adsorption of micronutrients on peat samples were evaluated by checking that the maximum adsorption occurred at pH 6.0, and the adsorption process follows a pseudo-second order kinetics and the Langmuir model was best fitted to the data obtained. The order of adsorption affinity in general was: Cu>Fe>Ni=Zn=Co>Mn. The release experiments of peat enriched in the aqueous and in the soil/plant system showed that the release of micronutrients follows, in general, the following order: Zn≥Fe>Mn>Co>Ni>Cu and in the pH 6.0 and for sample TSI the release were greater. The best complexing capacity was obtained at pH 4.5, whereas for the sample TSASH the quantities of micronutrients complexed were higher than for the sample TSISH. These differences are explained by the differences observed in the chemical molecular structure observed in the characterizations. The most stable complexes are formed with iron and the less stable with zinc, favoring the release of the latter. The polymer beads developed with peat and peat humic substances enriched with micronutrients showed satisfactory results and can be classified as slow-release fertilizers.